Improving Disaster Risk Reduction Preparedness and Resilience Approaches in Emergency Response Interventions in African Countries - Ernest Tambo (International Journal of Public Health Science (IJPHS), 2017)
Increasing globalization, increasing intense urbanization and climate changes have been linked to communities’ hazards and disasters vulnerabilities reported across Africa. Less data and information are documented on national to community disaster risk workforce readiness and resilience capacity in emergency humanitarian crises interventions. The lack of coherent and integrated disaster risk analysis and preparedness, response and recovery programs implementation is a major challenged in the region for decades. This paper highlights natural and man-made emergency hazards and disasters nature and exposure, potential approaches in Africa context. Our findings showed that man-made disasters events were the most documented, uneven in their nature, pattern and trend of occurrence and exposure consequences over time. Emerging and re-emerging outbreaks (Cholera, Polio, HIV, Ebola, Influenza, Rift Valley fever and Meningitis) were the most common, followed by conflicts and hunger, floods and land-sliding disproportionately spread across Africa. We also documented differential inadequacies in effective community risk assessment to emergency management, weak community disaster risk knowledge and attitudes to poorly integrated mitigation and recovery strategies. Leveraging on digital and social media network platforms advances coupled with existing fire, emergency facilities and proven effective hazard/disaster response lessons learnt and experiences are resources in strengthening laboratory capacity and laboratory networks, scaling up proactive displaced people/refugee security and safety standards support and best practice. Strengthening the national Sendai Framework for Disaster Risk Reduction (SDRRF) stewardship and investment (2015-2030) implementation is crucial in improving evidence-based, robust, and effective disaster risk reduction (DRR) community-based programs, in ensuring emergency public health readiness and resilient response capacities and ownership strategies in Africa.